2005
DOI: 10.1093/ejo/cji084
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial changes in Icelandic children between 6 and 16 years of age – a longitudinal study

Abstract: The aim of the present study was to describe the craniofacial changes between 6 and 16 years of age in a sample of Icelandic children. Complete sets of lateral cephalometric radiographs were available from 95 males and 87 females. Twenty-two reference points were digitized and processed by standard methods, using the Dentofacial Planner computer software program. Thirty-three angular and linear variables were calculated, including: basal sagittal and vertical measurements, facial ratio, and dental, cranial bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
1
12
0
4
Order By: Relevance
“…35 During a similar age interval, other studies also showed similar age-related changes in SBa. 31, 32 Henneberke and Prahl-Anderson also reported constant growth velocity for S-Ba over 7 years from age 7 to 14 at 1 mm/y and 0.9 mm/y for boys and girls, respectively; the average length of S-Ba was 2.5 mm larger in boys than in girls. 24 On the other hand, other studies showed slightly different growth rates in different age groups and suggested that cranial base growth was closely related to skeletal age.…”
Section: Results Of Individual Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…35 During a similar age interval, other studies also showed similar age-related changes in SBa. 31, 32 Henneberke and Prahl-Anderson also reported constant growth velocity for S-Ba over 7 years from age 7 to 14 at 1 mm/y and 0.9 mm/y for boys and girls, respectively; the average length of S-Ba was 2.5 mm larger in boys than in girls. 24 On the other hand, other studies showed slightly different growth rates in different age groups and suggested that cranial base growth was closely related to skeletal age.…”
Section: Results Of Individual Studiesmentioning
confidence: 93%
“…30 This was also supported by Thordarson et al, who showed no difference in cranial base flexure from age 6 to 16 years. 31 In a longitudinal study by Wilhelm et al, there was no difference reported in cranial base angle between different facial classifications, specifically Class I and Class II. 3,34 In one of the studies by Knott, she concluded that the decrease in WPO angle (which was defined as the angle between the postsphenoid line from P to O and the presphenoid line from W to P) and increase in postsphenoid length corresponded to the movement of the occipital condyle point.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations